Perceptions of graduates of a double-degree program in medicine and business administration on their levels of confidence and usefulness of their curriculum in clinical residency training - Dela Cruz, Amiel Cornelio E.; Sana, Erlyn A. (Manila The National Teacher Training Center for the Health Professions, University of the Philippines Manila, 2017)
A number of medical schools around the world now offer a dual degree of Doctor of Medicine and Master of Business Administration, in response to the need for management competencies for physicians. The Ateneo School of Medicine and Public Health (ASMPH) established in 2007, is the first in the Philippines to offer this dual degree. This study investigated the graduates? perceived levels of confidence and usefulness of the dual-degree program during residency training. Using the convergent parallel mixed methods design, quantitative data were collected from a survey while qualitative data were collected from focus group discussions (FGD) and key informant interviews (KII). ASMPH graduates from school years 2012 to 2013 undergoing residency training were surveyed with an 85.11 percent response rate. FGDs and KII were conducted with selected residents and training officers. Levels of confidence on their competencies, as well as the levels of usefulness of business administration topics in the curriculum were surveyed. Qualitative data were generated to compliment the survey. Survey data were analyzed using frequency counts, means, and mean ranks. Results showed that graduates of MD-MBA generally feel confident in all 18 program outcomes. Residents and consultants agree that these graduates are ?competent and confident leaders and effective communicators? more adept at leading, organizing and planning, and working with teams. The perceived levels of confidence do not vary significantly according to age, sex, and year level. Respondents in the ward-based specialties and surgical-based specialties were most confident in displaying interpersonal and communication skills as compared to respondents from Laboratory-based specialties who were more confident in functioning as supervisor, teacher and trainer. The perceived usefulness of the dual program did not vary significantly according to age and year level, but varied significantly according to sex, wherein male respondents found financial management as most useful compared to female respondents who found the dynamics of leadership as most useful. Respondents from ward-based specialties considered operations management as most useful while those from OR-based and Laboratory-based specialties considered the dynamics of leadership as most useful. The study proved that the MD-MBA is able to prepare physicians confident with their skills proficient in leadership, and systems-based approach to health care. Research studies focusing on how graduates of this dual degree program actually contribute to healthcare, and in comparison with graduates of the traditional medical curriculum are recommended.
Thesis (Master of Health Professions Education)--University of the Philippines Manila, May 2017
Panel Members: Erlyn A. Sana PhD, Chair/Adviser; Melflor A. Atienza MD MHPEd, Reader/Critic; Maria Elizabeth M. Grageda PTRP MHPED, Member; Christopher Joseph L. Soriano MD, MHPEd, Member; Jesus N. Sarol Jr. PhD, Member
Keywords: Medicine -- Study and teaching (Residency); Residency training